Interrelationship of Sarcopenia and Cardiovascular Diseases: A Review of Potential Mechanisms and Management - Rivera, Frederick Berro; Escolano, Bettina Therese; Nifas, Frances Micole; Choi, Sarang; Carado, Genquen Philip; Lerma, Edgar; Vijayaraghavan, Krishnaswami; Yu, Marc Gregory (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Sarcopenia refers to an age-related reduction of lean body mass. It showed a reciprocal relationship with cardiovascular diseases. Thus, it is imperative to explore pathophysiological mechanisms explaining the relationship between sarcopenia and cardiovascular diseases, along with the clinical assessment, and associated management. In this review, we discuss how processes such as inflammation, oxidative stress, endothelial dysfunction, neural and hormonal modifications, as well as other metabolic disturbances influence sarcopenia as well as its association with cardiovascular diseases. Moreover, this review provides an overview of both non-pharmacological and pharmacological management for patients with sarcopenia and cardiovascular diseases, with a focus on the potential role of cardiovascular drugs to mitigate sarcopenia.